TNF-α Inhibitor-Induced Psoriasis and Psoriatic Alopecia in Adolescent with Ulcerative Colitis: Clinical Case - Eduard T. Ambarchyan; Vladislav V. Ivanchikov; Anna L. Arakelyan; Andrey N. Surkov; Anastasia D. Kuzminova; Evgeny E. Bessonov; Elena V. Komarova ("Paediatrician" Publishers LLC, 2023)
Background. Genetically engineered biological therapy has revolutionized the treatment of many chronic inflammatory diseases. It often allows to achieve significant clinical effect and improve the patient's quality of life. However, sometimes it leads to adverse events, and physicians encounter them more often. One of such side effects is paradoxical psoriasis (PP) that can be revealed during the therapy with tumor necrosis factor alpha (TNF-α) inhibitors. PP is the debut or exacerbation of pre-existing psoriasis.Clinical case description. Patient A., 17 years old, has suffered from ulcerative colitis since 2020; biological therapy with infliximab has been initiated in March 2022. Numerous rashes were revealed, as well as development of confluent alopecia foci on the background of scalp psoriatic damage, during the next hospitalization in December 2022. The patient was examined by dermatologist; diagnosis of PP was established according to the clinical picture and medical history. Skin rashes progressed and ulcerative colitis worsened (diarrheal syndrome, fecal calprotectin levels increased up to 526 μg/g) after cessation of infliximab therapy. Biological therapy with the inhibitor IL-12/23 (ustekinumab) was initiated due to the aggressive cutaneous pathological process and the aggravation of inflammatory bowel disease (IBD) symptoms. The gradual regression of rashes with the restoration of scalp hair growth and ulcerative colitis clinical and laboratory remission were noted during the treatment.Conclusion. PP is a rare complication that develops during therapy with TNF-α inhibitors, and it is most often observed in patients with IBD. In our case there was aggressive course of psoriasis with severe scalp lesion and hair loss (it is specific type of lesion in such patients). The ustekinumab, inhibitor IL-12/23, treatment efficacy correlates with the literature data on this drug successful use in both nosologies. Ustekinumab can be a first-line therapy in such pediatric patients. This clinical case is the first case in the Russian literature on effective management of PP and ulcerative colitis with ustekinumab in children.